Pre-service teachers' agentive projections toward innovation in online English Language Teaching (ELT) classes - Farmasari, Santi; Wardana, Lalu Ali; Baharuddin, Baharuddin; Amrullah, Amrullah; Isnaeni, Mh; Lail, Husnul (REID (Research and Evaluation in Education), 2023)
This study examines the pre-service teachers' agentive projections toward innovation in online English Language Teaching (ELT) classes. Employing teacher agency theory, this instrumental case study views projections as agentive when they are informed by the students' ecological aspects (past and present), oriented to solve potential learning problems and improve learning outcomes. The study involved 84 pre-service teachers who were voluntarily asked to fill in a questionnaire, submit a lesson plan, and be interviewed. nVivo Pro was used to organize themes. The study indicates that the pre-service teachers, M=3.81, SD=.590, perceive that innovation in online ELT classes is closely related to the integration of information and technology. As a result, the students' agentive projections were also oriented to solve technology and internet-based obstacles, added with innovative learning methods. The research findings may become important insights for the development of English teaching and learning in order to provide more capital for pre-service teachers creating ELT innovation in the future.